Measuring Environmental Performance for Automobile Industry - Business Plan - Vedak, Amol (2009)
Idea: Due to the change in government regulation and consumer behaviour caused by the awareness of global warming, many organisations and sectors are given stringent targets to reduce the carbon emission and undertake environmental friendly processes. Automobile sector is one of the sectors that are highly affected due to these changes in the external environment. The academic as well as the personal research conducted suggest that, at present companies are moving in the direction by implementing process changes and measuring the changes using excel, access, spreadsheet etc. However, these tools are in-efficient and are not suitable for long term objective of the organisation. This has developed a niche market for the software that caters to the specific requirements of the automobile sector. As part of this proposal, I propose to built this software and fulfil the genuine requirement of the companies. The document covers the business plan associated with the idea mentioned above.